Relationship between short telomere length and stroke: A meta-analysis. Issue 39 (September 2018) - Jin, Xiao; Pan, Biqi; Dang, Xiaojing; Wu, Huanlin; Xu, Danping
Abstract: Background: Several epidemiological studies had been carried out in different population cohorts to estimate the relationship between the shortened telomere length and stroke. However, the results still remained dispute. Consequently, we conducted this meta-analysis to estimate the relationship between them. Methods: PubMed, EMBASE, and Web of Science were systematically searched for related articles to evaluate the association between "stroke" and "telomere length. STATA 12.0 software was used to perform the meta-analysis. The Cochran Q test and inconsistency index ( I 2 ) were used to assess the heterogeneity. Begg funnel plot and Egger test were used to assess publication bias. Results: The meta-analysis was composed of 11 studies, consisting of 25, 340 participants. We found a significant relationship between shortened telomere length and stroke (OR: 1.50, 95% CI: 1.13–2.0; P = .005); however, in the prospective and retrospective study subgroup, we did not find a statistical significant relationship between shortened telomere length and stroke (the prospective subgroup: OR: 1.41, 95% CI: 1–1.98; P = .051) (the retrospective subgroup: OR: 1.89, 95% CI: 0.96–3.72; P = .067).